Schooling Ain't Learning in Europe: A Club Convergence Perspective - Linda Glawe; Carlos Mendez (Comparative Economic Studies, 2022)
Convergence in human capital is a key precondition to achieve income convergence in the European Union; however, so far research on this topic has nearly been absent. Our paper contributes to the literature by investigating the human capital convergence dynamics within the EU over the period 1990–2016 using a nonlinear dynamic factor model. While we find evidence of absolute convergence with respect to the average years of schooling, we identify four convergence clubs with respect to learning outcomes, and the divergence across those four clubs is increasing over time. A subsequent analysis of the determinants of the learning clubs reveals that institutional and learning spillovers are decisive for whether an EU Member State is on a high or low human capital trajectory.
Keywords: R10; R11; R58; 330; Human capital; Learning; Club convergence; European Union; Institutional quality; Spillover effects